A passively mode locked thulium doped fiber laser using bismuth telluride deposited multimode interference. (12th April 2016) - Jung, M; Lee, J; Song, W; Lee, Y L; Lee, J H; Shin, W
Abstract: We proposed a multimode interference (MMI) fiber based saturable absorber using bismuth telluride at ∼2 μ m region. Our MMI based saturable absorber was fabricated by fusion splicing with single mode fiber and null core fiber. The MMI functioned as both wavelength fixed filter and saturable absorber. The 3 dB bandwidth and insertion loss of MMI were 42 nm and 3.4 dB at wavelength of 1958 nm, respectively. We have also reported a passively mode locked thulium doped fiber laser operating at a wavelength of 1958 nm using a multimode interference. A temporal bandwidth of ∼46 ps was experimentally obtained at a repetition rate of 8.58 MHz.